Patient and Provider Cocreation of Mobile Texting Apps to Support Behavioral Health: Usability Study - Arevian, Armen C; O'Hora, Jennifer; Rosser, James; Mango, Joseph D; Miklowitz, David J; Wells, Kenneth B (JMIR Publications, 2020)
BackgroundMobile technologies hold potential for improving the quality of care and engagement of patients. However, there are considerable challenges in ensuring that technologies are relevant, useful, and engaging. While end users such as patients and providers are increasingly involved in the design of health technologies, there are limited examples of their involvement in directly creating technologies for their personal use. ObjectiveWe aim to evaluate the feasibility and acceptability of patients and providers creating mobile texting apps to support treatment goals. MethodsIn an 11-month usability study, we enrolled 4 providers and 28 patients in an intensive outpatient program for obsessive-compulsive disorder. Patients and providers created their own mobile texting apps using a visual app development platform. A subsample of 10 patients and 4 providers completed a usability measure. ResultsParticipants created a total of 360 unique mobile text messages (1787 total messages sent). There were 4 types of messages identified, including personalized reminders, clinical exposures, interactive prompts, and encouraging/informational messages. A total of 9 out of 10 (90%) patients agreed that the messages were relevant to their recovery, and 8 out of 10 (80%) agreed that the messages were effective at helping complete treatment plans. ConclusionsEnabling patients and providers to cocreate apps for their own use by using a visual application platform is feasible and holds potential for increasing the relevance, sustainability, and effectiveness of digital health technologies.